Analisis Penggunaan Sosial Media Pada Hasil Belajar Siswa SD Kelas VI - Ririn Damayanti; Meli Saputri; Nuralipah; Yayan Alpian (UNIB Press, 2024)
This study examines the use of social media by grade VI students at SDN Karawang Wetan I on their learning outcomes. This research uses descriptive qualitative research methods. The subjects of this study were grade VI students of SDN Karawang Wetan I. The data collection methods consisted of observation, interviews, questionnaires, and documentation. Data analysis by means of data reduction, data presentation, and drawing conclusions and suggestions. The results of this study indicate that the use of social media can affect student learning outcomes. As many as 58% of students use social media and most of them use the TikTok application. The duration of time used by students in using the application is more than one hour. This has an impact on the lack of study time they have.